A Global View of Business Insolvency Systems - Westbrook, Lawrence; Booth, Charles D.; Paulus, Christoph G.; Rajak, Harry (Washington, DC: World Bank and Brill, 2013)
The purpose of this book is to provide a coherent overview of the insolvency systems found around the world. Its intended audience includes academics, judges, lawyers, and policymakers. Its focus is on businesses rather than natural persons. The authors hope to give the reader a sense of some of the principal approaches to managing the general default of a business debtor. The authors will discuss the nature of the costs and benefits arising from the various policy choices legislators have made. In the process, they will emphasize the close interrelationship among various elements of an insolvency regime so that these elements can be viewed as part of an overall system and not just as a series of policy decisions about particular rules, such as the method of initiation of an insolvency case or the balance struck in setting the boundaries of an avoidance power. The organization of the book reflects our view of insolvency laws as complete systems, including not only the 'insolvency' or 'bankruptcy' code of a jurisdiction but also closely related laws and the institutional framework in which those laws are applied. The book takes a systematic approach to a variety of topics related to credit and insolvency regulation. The functional analysis starts with the study of debt enforcement, continues with an examination of general corporate insolvency legislation, corporate rehabilitation proceedings, informal workouts, employee rights, judicial and administrative institutions, and the considerations key to cross-border insolvency proceedings.